Two new species of planktonic Caligus O.F. Müller 1785 (Copepoda: Caligidae) from Türkiye with an updated review and checklist of planktonic caligids - Özak, Argun Akif; Kurt, Tuba Terbiyik; Kamanli, Seyit Ali; Akbulut, Gürkan; Yanar, Alper; Boxshall, Geoffrey A. (Zootaxa, 2024)
Two new species of caligid sea lice, Caligus izmiriensis sp. nov., and Caligus sarosensis sp. nov. are described, based on specimens collected from the zooplankton in the Gulf of Sığacık and the Gulf of Saros off the Aegean Sea coast of Türkiye. Detailed examination of the morphology of these two new species and comparisons with other closely related caligid species, especially Metacaligus yucatanensis Suárez-Morales, Kim & Escamilla, 2012, resulted in the recognition of the genus Metacaligus Thomsen 1949 as a junior synonym of Caligus O.F. Müller, 1785. Based on this proposed synonymy, all species of the genus Metacaligus are here transferred to Caligus: Metacaligus trichiuri (Krøyer, 1863), M. rufus (Wilson, 1908), and M. unguidentatus (Rangnekar & Murti, 1950) all return to their original combinations as Caligus trichiuri Krøyer, 1863, Caligus rufus Wilson, 1908, and Caligus unguidentatus Rangnekar & Murti, 1950, respectively; Metacaligus yucatanensis Suárez-Morales, Kim& Escamilla, 2012, becomes Caligus yucatanensis (Suárez-Morales, Kim & Escamilla, 2012) comb. nov.; transferring Metacaligus latus Ho & Lin, 2002 would create a secondary homonym of Caligus latus Byrnes 1987, so a replacement name is proposed as Caligus cultellus nom. nov. We recognise C. yucatanensis as a member of the C. undulatus-group. The four other species previously placed in Metacaligus form a cluster which represents a new species group, the Caligus trichiuri-group. An updated list of planktonic caligids is presented, together with keys to species of the C. undulatus-group and of the newly proposed C. trichiuri-group. The subgenus Subcaligus Heegaard, 1943 was originally proposed to accommodate Caligus (Subcaligus) bocki Heegaard, 1943, and was characterised by its unusual stylet-like sternal furca. This subgenus has not been treated as valid by subsequent authors and we here formally propose to treat Subcaligus Heegaard 1943 as a junior synonym of Caligus.